Financial Deepening, Banking Stability and Cross-border M&A Activity - Evidences from Emerging Countries - Wen, Shiow-Ying (Journal of Economics and Behavioral Studies, 2014)
This study investigates the effect of financial deepening, banking stability and market structure on cross-border M&A activity in 13 emerging countries with data covering the period, 2003-2010. We show the empirical results of panel regression by sub grouping portfolio based on whether the firms are acquirer or target to cross-border M&A activity. For acquiring countries, the results show a significantly positive effect of the deepening indicator in cross-border M&A activity. Moreover, bank stability on the acquiring firms investing in the cross-border M&As shows a significantly positive effect. For targeting countries, the results show a significantly positive impact of the deepening indicator in cross-border M&A activity. A positive relation between the ratio of the amount of credit provided by banks and other financial institutions to the private sector to GDP in cross-border M&A activity is found as well. These findings imply that not only financial depth but also banking stability promotes cross-border M&A activity for emerging economies.